2022
DOI: 10.3390/nu14142996
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Caffeine Supplementation on Physical Performance, Physiological Responses, Perceived Exertion, and Technical-Tactical Skills in Combat Sports: A Systematic Review and Meta-Analysis

Abstract: Although the effects of caffeine supplementation on combat sports performance have been extensively investigated, there is currently no consensus regarding its ergogenic benefits.This systematic review with meta-analysis aimed to summarize the studies investigating the effects of caffeine supplementation on different aspects of performance in combat sports and to quantitatively analyze the results of these studies to better understand the ergogenic effect of caffeine on combat sports outcomes. A systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 146 publications
4
21
1
Order By: Relevance
“…Our behavioral data reinforce the evidence that systemic caffeine administration is ergogenic [2-5, 7, 16]. However, we emphasize that this previous knowledge analyzed treadmill running performance, and we demonstrate here for the first time that caffeine increases (grip) muscle strength in mice, an effect well observed in humans [27,28]. Also, we demonstrated that local caffeine treatment in the striatum reproduces these ergogenic effects (systemic treatment) for the first time.…”
Section: Discussionsupporting
confidence: 90%
“…Our behavioral data reinforce the evidence that systemic caffeine administration is ergogenic [2-5, 7, 16]. However, we emphasize that this previous knowledge analyzed treadmill running performance, and we demonstrate here for the first time that caffeine increases (grip) muscle strength in mice, an effect well observed in humans [27,28]. Also, we demonstrated that local caffeine treatment in the striatum reproduces these ergogenic effects (systemic treatment) for the first time.…”
Section: Discussionsupporting
confidence: 90%
“…As exclusion criteria, the fact that they were using some type of illicit ergogenic resource and had some type of symptomatic cardiorespiratory or cardiac disease was considered. Female athletes did not participate, because in women, alterations in CA metabolism can occur, which may lead to a reduction in the ergogenic effects of CA, due to the interaction of the supplement with female sex hormones [ 19 ], especially in women who use contraceptives [ 23 ]. The athletes participated in the study voluntarily and signed an informed consent form, under the resolution 466/2012 of the National Research Ethics Commission—CONEP, of the National Health Council, following the ethical principles expressed in the Declaration of Helsinki (1964, reformulated in 1975, 1983, 1989, 1996, 2000, 2008, and 2013) from the World Medical Association.…”
Section: Methodsmentioning
confidence: 99%
“…It is common for athletes, both conventional and Paralympic, to consume supplements to improve performance [ 7 , 17 , 18 ]. Among the supplements, caffeine (CA) is an ergogenic agent widely used to improve the performance of high-intensity physical exercises [ 19 , 20 ]. Moreover, following the removal of CA from the World Anti-Doping Agency’s list of prohibited supplements, consumption of CA in competitions has increased significantly from 2004 to 2015 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations